2021
DOI: 10.1139/cjfas-2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water temperature and biotic interactions on the distribution of westslope cutthroat trout (Oncorhynchus clarkii lewisi) in a population stronghold under climate change

Abstract: Climate warming is expected to have substantial impacts on native trout across the Rocky Mountains, but there is little understanding of how these changes affect future distributions of co-occurring native fishes within population strongholds. We used mixed-effects logistic regression to investigate the role of abiotic (e.g., temperature) and biotic factors (Bull Trout presence, Salvelinus confluentus) on distributions of Westslope Cutthroat Trout (Oncorhynchus clarkii lewisi; WCT) in the North Fork Flathead R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 174 publications
(361 reference statements)
0
5
0
Order By: Relevance
“…Due to climate change, westslope cutthroat trout may experience shifts in the distributions of their thermal habitat (Williams et al, 2009;Heinle et al, 2021). In order to simulate changes to species distributions and inform recovery strategies and actions, particularly for species at risk, it is important to understand a species' physiology and thermal limits.…”
Section: Discussionmentioning
confidence: 99%
“…Due to climate change, westslope cutthroat trout may experience shifts in the distributions of their thermal habitat (Williams et al, 2009;Heinle et al, 2021). In order to simulate changes to species distributions and inform recovery strategies and actions, particularly for species at risk, it is important to understand a species' physiology and thermal limits.…”
Section: Discussionmentioning
confidence: 99%
“…Such community approaches are necessary as single-species studies often overlook biotic interactions (such as indirect food web interactions) that are critical for realistic projections 15,16 . While most research has focused on how species distribution and population demography vary with abiotic conditions [17][18][19] , recent work demonstrated that accounting for biotic interactions (such as predation or competition) improves the projection of species responses to change 15,16 . Yet, few studies have examined the combined effect of projected changes in land use and in climate on multi-species trophic interactions 20 .…”
Section: Main Textmentioning
confidence: 99%
“…Spatiotemporal simulations of community dynamics are a powerful approach to gain a mechanistic understanding of how environmental changes can influence species interactions 13,14 . Such community approaches are necessary as single-species studies often overlook biotic interactions (such as indirect food web interactions) that are critical for realistic projections 15,16 . While most research has focused on how species distribution and population demography vary with abiotic conditions [17][18][19] , recent work demonstrated that accounting for biotic interactions (such as predation or competition) improves the projection of species responses to change 15,16 .…”
Section: Main Textmentioning
confidence: 99%
“…Spatiotemporal simulations of community dynamics are a powerful approach to gain a mechanistic understanding of how environmental changes can influence species interactions (Oliver et al, 2009; Tylianakis et al, 2008). Such community approaches are necessary as single‐species studies often overlook biotic interactions (such as indirect food web interactions) that are critical for realistic projections (Heinle et al, 2021; Trainor & Schmitz, 2014). While most research has focused on how species distribution and population demography vary with abiotic conditions (Bonnot et al, 2018; Dainese et al, 2017; Zurell et al, 2018), recent work has demonstrated that accounting for biotic interactions (such as predation or competition) improves the projection of species responses to change (Heinle et al, 2021; Trainor & Schmitz, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Such community approaches are necessary as single‐species studies often overlook biotic interactions (such as indirect food web interactions) that are critical for realistic projections (Heinle et al, 2021; Trainor & Schmitz, 2014). While most research has focused on how species distribution and population demography vary with abiotic conditions (Bonnot et al, 2018; Dainese et al, 2017; Zurell et al, 2018), recent work has demonstrated that accounting for biotic interactions (such as predation or competition) improves the projection of species responses to change (Heinle et al, 2021; Trainor & Schmitz, 2014). Yet, few studies have examined the combined effect of projected changes in land use and in climate on multispecies trophic interactions (Bossier et al, 2021).…”
Section: Introductionmentioning
confidence: 99%